2019
DOI: 10.1001/jamainternmed.2018.7653
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Google Translate for Spanish and Chinese Translations of Emergency Department Discharge Instructions

Abstract: Dr Khoong had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. Study concept and design: Khoong, Brown, Fernandez.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 6 publications
(9 reference statements)
2
71
0
1
Order By: Relevance
“…A recent study examines the use of Google Translate for translating emergency department discharge instructions from English into Chinese and Spanish (Khoong et al, 2019). The results showed that 2% of Spanish translations and 8% of translations into Chinese were inaccurate and could potentially cause significant harm (p. 580).…”
Section: Evaluation Of Mtmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study examines the use of Google Translate for translating emergency department discharge instructions from English into Chinese and Spanish (Khoong et al, 2019). The results showed that 2% of Spanish translations and 8% of translations into Chinese were inaccurate and could potentially cause significant harm (p. 580).…”
Section: Evaluation Of Mtmentioning
confidence: 99%
“…Chen et al (2017) assess just three sentences, for instance, and the simpler sentences among them do not necessarily concern diabetes or indeed a healthcare setting (p. 4). 8 In Khoong et al (2019) and Das et al (2019), the assessment involved back-translating the Google Translate output into English. This is a problematic method.…”
Section: Evaluation Of Mtmentioning
confidence: 99%
“…Although some health organisations provide portals in a range of languages, clinical notes are typically offered in one language only. Online machine translation, while improving,19 is subject to significant error rates, particularly if translating complex syntax and vocabulary in notes. Nevertheless, access to open notes appears to help some patients who speak another primary language by allowing them, or a care partner, to read and recall information 2 6.…”
Section: Opportunity To Improve Health Equitymentioning
confidence: 99%
“…By using DCAT before the consultation in a waiting room, the actual appointment is not disturbed or prolonged. This also distinguishes our approach from those which introduce a digital ad-hoc translation (e.g., using Google translate during the consultation) [28][29][30] and apps that only allow health care providers to communicate preselected phrases and are therefore not self-administered by patients [14,15,17,18]. Furthermore, the DCAT app is free to download, making it accessible to all clinics that have a digital device they can circulate.…”
Section: Discussionmentioning
confidence: 99%